2010
DOI: 10.1016/j.pharmthera.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of cognitive dysfunction and negative symptoms of schizophrenia: Focus on NMDA receptor antagonism

Abstract: Cognitive deficits in schizophrenia remain an unmet clinical need. Improved understanding of the neuro-and psychopathology of these deficits depends on the availability of carefully validated animal models which will assist the development of novel therapies. There is much evidence that at least some of the pathology and symptomatology (particularly cognitive and negative symptoms) of schizophrenia results from a dysfunction of the glutamatergic system which may be modelled in animals through the use of NMDA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
333
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(362 citation statements)
references
References 167 publications
19
333
3
7
Order By: Relevance
“…With respect to cognitive impairment, numerous preclinical studies have shown that ketamine impairs cognition in rodents and nonhuman primates, effects similar to those reported in humans (Buccafusco and Terry, 2009;Neill et al, 2010;Roberts et al, 2010;Taffe et al, 2002a). In contrast, the effects of NR2B NAMs have been less well studied and have produced mixed results.…”
Section: Introductionmentioning
confidence: 83%
“…With respect to cognitive impairment, numerous preclinical studies have shown that ketamine impairs cognition in rodents and nonhuman primates, effects similar to those reported in humans (Buccafusco and Terry, 2009;Neill et al, 2010;Roberts et al, 2010;Taffe et al, 2002a). In contrast, the effects of NR2B NAMs have been less well studied and have produced mixed results.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, a common preclinical model of schizophrenia involving transient blockade of N-methyl-D-aspartate receptors (NMDARs) with repeated administration of NMDAR antagonists during a critical period of adolescent development induces profound and lasting deficits in LTD at synapses from the hippocampus to PFC (Ghoshal and Conn, 2015;Thomases et al, 2014). This has been postulated to contribute to the increased activity of PFC neurons observed following phencyclidine (PCP) treatment in rodents (Katayama et al, 2007;Suzuki et al, 2002;Thomases et al, 2014;Wang et al, 2007) as well as the subsequent behavioral changes associated with negative and cognitive symptoms in the disorder (Neill et al, 2010(Neill et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…PCP treatment of rodents over both acute (Ernst et al, 2012;Neill et al, 2010) and chronic (Hashimoto et al, 2005;Marquis et al, 2003;Murai et al, 2007;Qiao et al, 2001) intervals is thought to induce a psychosis-like state through blockade of N-methyl-Daspartate (NMDA) receptor activity, which results in altered levels of glutamate and increased dopamine. Alterations in glutamatergic and dopaminergic neuronal transmission in the stratium and frontal cortex have been implicated in the etiology of human SCZ, and the model was derived from observations of acute psychotomimetic effects of PCP in healthy humans and exacerbation of symptoms in chronic SCZ patients (Lahti et al, 1995;Mouri et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%